Case Study and Qualitative Comparison of Global Legal Frameworks for Platform Labor - Koo, Byeongsu; Lee, Jooyeoun; Chung, Myoungsuk (Proceedings of the IEEE International Conference on Big Data and Smart Computing, BIGCOMP, 2025)
This study investigates the legal and policy responses of countries to platform labor, a significant employment form in the digital economy. Platform workers often fall into the gaps of traditional labor laws, facing challenges such as unclear legal status, limited social insurance coverage, insufficient algorithm transparency, and weak regulatory enforcement. Using fuzzy-set qualitative analysis, this study examines platform labor policies in the United States, Japan, and China. Japan recognizes platform workers as an intermediate category under the Specified Fiduciary System, offering partial legal protections. China adopts a comprehensive but weakly enforceable framework under the concept of New Employment Forms. Meanwhile, the U.S. demonstrates variability across states, with conflicts between recognizing platform workers as employees versus independent contractors. Based on these findings, the study proposes policy recommendations to improve platform worker protections, emphasizing clearer legal definitions, enhanced social insurance inclusion, greater algorithmic transparency, and stronger enforcement mechanisms.
Keywords: Case-studies; Digital economy; Fuzzy-set qualitative analyze; Labor laws; Legal frameworks; Legal status; Platform labor; Qualitative analysis; Worker protection; Workers; digital economy; fuzzy-set qualitative analysis; platform labor; worker protection